متطلبات الاعتماد الأكاديمي لمعيار - الجرايدة, دلال (جامعة الوادي University of Eloued, 2018)
هدفت الدراسة إلى التعرف على درجة توافر متطلبات الاعتماد الأكاديمي لمعيار (الرسالة والغايات والأهداف) في كلية التربية بجامعة طيبة من وجهة نظر أعضاء هيئة التدريس, ولتحقيق أهداف الدراسة استخدمت الباحثة المنهج الوصفي، وعليه تم بناء استبانة مكونة من (22) فقرة موزعة على خمسة محاور، وبعد جمع البيانات وتحليلها أظهرت النتائج أن تقديرات أفراد العينة لدرجة توافر متطلبات الاعتماد الأكاديمي لمعيار (الرسالة والغايات والأهداف) على أداة الدراسة ككل جاءت بدرجة متوسطة, كما أظهرت النتائج عدم وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α =0,05) في تقديرات أفراد العينة, على الأداة ككل تعزى لأثر الجنس، كما أظهرت النتائج عدم وجود فروق ذات دلالة إحصائية لأثر الرتبة العلمية على الأداة ككل. The study aimed to identify the degree of availability of academic accreditation standard (mission, goals and objectives) in the college of Education, University of taibahu as perceived by academic staff. And to achieve objectives of the study, the researcher used the descriptive approach requirements. A questionnaire was used and it was composed of(22) items distributed on five axes, the study sample was a random selection of(114) faculty members and after data collection and analysis showed It results that the sample estimates of the degree of availability of academic accreditation standard requirements(mission, goals and objectives) to study the tool as a whole came moderately the results also showed a statistically significant no differences at the significance level (α=0.05) in the sample estimates of the tool as a whole due to the impact of sex, as results showed no differences statistically significant in the impact of rank on the tool.
الرسالة والغايات والأهداف
مقال
Keywords: متطلبات؛ المعيار؛ الرسالة والغايات والأهداف؛ الاعتماد؛ الاعتماد الأكاديمي; requirements; academic accreditation; standard; mission; goals and objectives